Phytochemical and biological evaluation of defatted seeds of Jatropha curcas - ul Haq, Muhammad Nisar; Wazir, Sultan Mehmood; Ullah, Faizan; Khan, Rahmat Ali; Shah, Mir Sadiq; Khatak, Adnan (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this study, the antimicrobial, antioxidant, phytotoxic and phytochemical properties of defatted seeds of Jatropha curcas were evaluated. A crude methanolic extract of defatted seeds was tested against three fungal strains - Aspergillus niger, Aspergillus flavus and Aspergillus fumigatus - and five bacteria: Escherichia coli and Klebsiella pneumoniae (Gram-negative) and Micrococcus luteus, Bacillus subtilis and Staphylococcus aureus (Gram positive). The methanolic extract was diluted in dimethylsulfoxide to final concentrations of 1, 2, 3, 4 and 5 mg/10 mL. The largest zones of inhibition against K. pneumoniae, M. luteus and B. subtilis were achieved using the concentration of 5 mg/10 mL. The concentration of 1 mg/10 mL was most effective against S. aureus and E. coli. In a 1, 1-diphenyl-2-picrylahydrazyl (DPPH) radical scavenging assay, the 5 mg/10 mL concentration of the Jatropha seed extract showed the strongest activity. Higher concentrations of the Jatropha seed extract (10 mg/50 mL and 5 mg/50 mL) significantly inhibited the germination of radish seeds and had negative effects on radish seedling relative water content, shoot length, root length, seedling fresh weight and seedling dry weight (p<0.05). Phytochemical analyses of the defatted seeds detected alkaloids (7.3%), flavonoids (0.39%) and soluble phenolics (mg gallic acid equivalents/g extract). Based on these results, it was inferred that J. curcas seeds contain active ingredients that are effective against pathogenic microbes and therefore could be used to formulate drugs to treat various diseases.